A study on palm oil moisture absorption level and voltage breakdown [electronic resource] - Nur Syamimi Murad, 1990-, author (2013)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2013